Apuntes sobre el arbitraje en China y el reconocimiento de laudos - Tam Pérez, José (2017)
This paper is about the arbitration in China ant he recognition of the foreign arbitral awards in China and Peru. The author indicates how the arbitration and the dispute settlement were in China, also he says that the Chinese commercial opening produced that China adopted inside its legal system the commercial arbitration. Above this line, he says that the main instrument regarding the recognition and enforcement of the foreign arbitral awards in China and Peru is the New York Convention. About the proceeding of this recognition and enforcement of the foreign arbitral awards it is said how it is performed in the Chinese and Peruvian Law. The author ads that China and Peru should have a mutual awareness proceeding of the dispute settlement to ensure the mutual investments.